Is There a Narrator in This Narrative? - Myriam BOUSSAFSAF (Revue des Sciences Humaines)
Some narratologists insist on the fact that a narrative cannot do without a narrator that has to be distinguished from the real author. Indeed, the narrator is considered as that mediating agency whose task is to prepare the reader’s entrance to the diegetic world by organizing all the necessary elements which may facilitate this entrance. This is what has been labelled the pan-narrator theory.